207 - INJURIES OF THE ARTICULATION OF KNEE OCCURRED IN PRACTICE OF RECREATINAL SOCCER IN SANTAREM IN THE PARA STATE (Fiep Bulletin - online, 2011)
This study is retrospective and it is characterized as a descriptive and inferential research with the using of qui-square of Peterson to set up a correlation. The objective of this work was to do a survey of the prevalence of the injuries of the articulations of the knee through the using of methods such as questionnaire, anamnesis and the exam of magnetic resonance to correlate them with the time of practice in this modality. The sample comprehended 30 practice of recreational soccer between 20 and 45 years old, who suffered injuries in the period from January 1st of 2006 to December 30th of 2008. The found results demonstrated that 83,33% of occurred injuries are of anterior cruciate ligament, medial meniscus, 16,67% of all the injuries associations. It follows that the less time used to practice of recreational soccer, the more incidence of injuries will occur, having as correction of p< 0,0001.
Keywords: Knee; soccer; magnetic resonance